Incidence and Predictors of Perioperative Complications With Transvenous Lead Extractions: Real-World Experience With National Cardiovascular Data Registry. (February 2018) - Sood, Nitesh; Martin, David T.; Lampert, Rachel; Curtis, Jeptha P.; Parzynski, Craig; Clancy, Jude
Abstract : Background: Transvenous lead extraction is an integral part of management of patients with cardiovascular implantable electronic devices. Real-world incidence and predictors of perioperative complications in extractions involving implantable cardioverter-defibrillator leads have not been described in detail. Methods and Results: Data from the National Cardiovascular Data Registry Implantable Cardioverter-Defibrillator Registry were analyzed. Lead extraction was defined as removal of leads implanted for >1 year. Predictors of major perioperative complications for all extraction procedures (11 304) and for high-voltage lead (8362, 74%), across 762 centers, were analyzed using univariate and multivariate logistic regression. Major complication occurred in 258 (2.3%) extraction procedures. Of these 258 with a complication, 41 (16%) required urgent cardiac surgery. Of these 41, 14 (34%) died during surgery. Among the total 98 (0.9%) deaths reported, 18 (0.16% of total) occurred during transvenous lead extraction. In multivariable logistic regression analysis, female sex, admission other than electively for procedure, ≥3 leads extracted, longer implant duration, dislodgement of other leads, and patient's clinical status requiring lead extraction (infection/perforation) were associated with increased risk of complications. Smaller lead diameter, flat versus round coil shape, and greater proximal surface coil area were multivariate predictors of major perioperative complications specific to high-voltage leads. Conclusions: The rate of major complications and mortality with transvenous lead extraction is similar in the real-world outcomes to that reported in recent single-center studies from high-volume centers. There is significant risk of urgent cardiac surgery, which carries a high mortality, and planning for appropriate cardiothoracic surgery backup is imperative. Abstract : Supplemental Digital Content is available in the text.